2015
DOI: 10.3390/su7010683
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Land Management: An Analysis of Stakeholder Perceptions in Rural Northern Germany

Abstract: Successful sustainable land management efforts rely on stakeholder support and integration of stakeholder knowledge. This study explored the views of sustainable land management expressed by land use stakeholders and how these views contribute to land users' self-perceptions. We examined stakeholder perceptions in four case study areas in rural northern Germany. The target groups consisted of representatives from (i) agriculture; (ii) forestry; (iii) water management and (iv) rural planning and development ("c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…While it is unwarranted to suggest that the community of West Yellowstone is not concerned with future generations, their continued focus on the economy and extra-local influences has created an environment where it is not a vocalized priority. Similar to what Lange et al (2015) found in northern Germany, shorter term concerns are more critical to residents' thinking at the present time, despite the fact that long-term planning will ensure a more successful transition toward sustainability.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…While it is unwarranted to suggest that the community of West Yellowstone is not concerned with future generations, their continued focus on the economy and extra-local influences has created an environment where it is not a vocalized priority. Similar to what Lange et al (2015) found in northern Germany, shorter term concerns are more critical to residents' thinking at the present time, despite the fact that long-term planning will ensure a more successful transition toward sustainability.…”
Section: Discussionmentioning
confidence: 53%
“…Using four case studies in rural Germany, Lange et al, (2015) studied the perceptions of representatives from the agriculture, forestry, water management, and planning sectors. The authors' found that societal dimensions of sustainability were underrepresented in the perceptions of all these stakeholder groups, that economic dimensions were prioritized by most (especially land managers), and that environmental dimensions were often contextualized in regard to resource availability as opposed to biological diversity.…”
Section: Sustainability and Perceptionsmentioning
confidence: 99%
“…Landscapes are typically impacted by multiple disturbances that operate at different spatial and temporal scales [13,14]. Therefore, in contrast to general ecological risk assessment, landscape ecological risk assessment comprehensively assesses various types of potential ecological impacts, and their cumulative effects.…”
Section: Introductionmentioning
confidence: 99%
“…These arguments suggest that the endemic developmental problems of rural areas constitute a distinct demand-side rationale for nonprofit organizations, a rationale that constitutes the ultimate, if implicit, core of the theoretical justification of rural partnerships as a rural development policy instrument (cf. [55][56][57]). …”
Section: Rurality and The Nonprofit Sectormentioning
confidence: 99%